A service learning relationship fostering cultural competancy: The cultural immersion of occupational therapy students and reflective practice - Goddard, Trevor; Gribble, Nigel (Curtin University of Technology, 2006)
Reflective practice has been the learning and teaching instrument fostering cultural competence for 50 Curtin University Occupational Therapy students who have participated in a four week service learning placement at the Shanghai Boai Children’s Rehabilitation Centre in China since 2001. Graduates from Curtin University are expected to demonstrate cultural awareness and understanding. This paper postulates that reflective journals and group collaborative leadership are learning and teaching tools within a service learning relationship that engage students in developing cultural competence in alternative social, cultural and health service milieus. While immersion is a recognised method of fostering cultural competence, alone it does not promote rich engagement with clients, the desire to understand, and enable confidence through sustained effort. Reflective practice links academic learning and clinical practice for students, allowing them to explore and change attitudes toward clients and develop clinical cultural competencies within the service learning relationship. The strength of this program is the fusion of service learning and reflective practice; where action learning forms an integral part of developing cultural competency. The program incorporates learning and assessment practice which includes individual journals and collaborative leadership development, language and cultural orientation sessions, a stepped transition from facilitator supervised to independent practice and a collaborative group environmental scan of the Chinese health system to enhance the cultural competency of students.